Evaluation of antioxidant, antimicrobial activities and phytochemical content of some Egyptian plants - Rashed, K. (2020)
This study evaluated antioxidant and antimicrobial activities of methanol extracts of Artocarpus heterophyllus, Parkia africana, Derris rubosta and Cichorium intybus stems and also phytochemical analysis of the four plants was detected. Antioxidant activity was evaluated by radical scavenging assay and phosphomolybdenic assay. Total phenolics and flavonoids were estimated by Folin-Ciocalteu reagent and aluminium chloride method. The antimicrobial screenings were carried out via disc diffusion method and minimal inhibition concentration against three species of gram negative bacteria: Escherichia coli CCM 3988, Salmonella enterica subsp. enterica CCM 3807, Yersinia enterocolitica CCM 5671 and three grampositive bacteria: Bacillus thuringiensis CCM 19, Listeria monocytogenes CCM 4699, Stapylococcus aureus subsp. aereus CCM 2461. All the plants tested had some antioxidant activity. Parkia africana had the highest antioxidant activity values of 47.99 μg TEAC/g and 1036.56 μg TEAC/g in the DPPH• and phosphomolybdenum assays respectively; along with the highest amount of total flavonoids (0.165 μg QE/g). The inhibition zones against three gram-negative strains of different tested plants were ranged from 10-24 mm. From our results the Parkia africana extract showed the strongest action against E. coli (24 mm), S. enterica subsp. enterica (21 mm) and Y. enterocolitica (22 mm). The minimum inhibitory affect of plants ranged from 16 to 256 µg/ml. The best antibacterial activity was found at Parkia africana against gramnegative bacteria strains. The results indicated that the plants tested may be potential sources for isolation of natural antioxidant and antimicrobial compounds.